HUBUNGAN FAKTOR LINGKUNGAN DENGAN PERSEBARAN KEJADIAN DEMAM BERDARAH DENGUE (DBD) DI KECAMATAN JEPARA KABUPATEN JEPARA - Zulmi Indriyani; Mursid Rahardjo; Onny Setiani (Jurnal Kesehatan Masyarakat (Undip), 2017)
Dengue Hemorrhagic Fever (DHF) was an important health issue in the world, particularly in tropical countries such as Indonesia. Jepara was one of the city that has relatively high cases of DHF every year. In 2013, jepara had the highest cases among the cities in central java with IR 183.6/100,000 capita and CFR of 12,5 %. District in jepara that has highest case is jepara subdistrict. Environmental factor such as physical, bilologi and sosial are considered as a major factor that influencing the high number of DHF cases. In this researh, SIG analyses is perfomed to detemine the relationship between environment and DHF cases in the jepara subdistrict.The aim of this research is to analyze and mapping the spatial distribution of the relationship between environmental factor with DHF cases in Jepara subdistrict. This researh was a observasional research with case control reseach design. The sample of research was obtained from 72 respondents (36 cases and 36 control). The data was analysed using univarriate method, bivariate method with chi-square and spatial method to map the case of DHF.According to the result, there was 52,8% houses with air at risk, 91,7% houses with humidity at risk, 81,9% respondent’s houses with House Index at high risk, 55,3% respondents with Container Index at high risk and 70,8% respondents that have less behaviour to DHF.There is a tendency that high rainfall will cause the high case of DHF. There is no significant relatioship between temperature of house with the case of DHF p-value 0.345 OR (0.643). theres is no significant relationship between moisture of the house with the case of DHF p-value 0,674 OR(2,125). There is relatiopship between House Index (HI) with the case  DHF p-value 0,006 OR(7,480). There is relantionship between Container Index (CI) with the case DHF p-value 0,001 OR(5,588). There is relationship between behavior of respondents with  the case DHF p-value 0,007 OR(3,912).The conclution of this research is that there is relationship between HI, CI and behavior with the case of DHF. So, the PSN awarness should be necessarily improved in order to change the bad behaviour of society and thus the number of HI and CI can be reduced.